Communicable Diseases (Including COVID-19)—Induced Global Depression: Caused by Inadequate Healthcare Expenditures, Population Density, and Mass Panic - Anser, Muhammad Khalid; Yousaf, Zahid; Khan, Muhammad Azhar; Sheikh, Abdullah Zafar; Nassani, Abdelmohsen A.; Abro, Muhammad Moinuddin Qazi; Zaman, Khalid (Frontiers in Public Health, 2020)
Coronavirus (COVID-19) is spreading with an enormous rate and has caused the deaths beyond expectations due to varied reasons, probably, i) an inadequate healthcare spending, for instance, shortage of protective types of equipment, testing swabs, masks, surgical gloves, gowns, etc; ii) high population density that cause close physical bindings among the community members, which, reside in compact places, hence they are likely to expose with communicable diseases including coronavirus, and iii) mass panic due to fear of being the loss of loved ones, lockdown, and shortage of foodstuff. In a given scenario, the study focused on the following key variables, i.e., communicable diseases, healthcare expenditures, population density, poverty, economic growth, and (COVID-19) dummy variable in a panel of 76 selected countries from 2010 through 2019. The results show that the impact of communicable diseases on economic growth is although positive because the infected countries get reap of economic benefits from the other countries in the form of receiving healthcare technologies, knowledge transfers, cash transfers, international loans, aid, etc., to may able to get out of the diseases. However, the case is different with (COVID-19) as it seizes the whole world together in a very shorter period of time and no other countries could be able to help others in terms of giving funding loans, healthcare facilities, and technology transfers. Thus, the impact of (COVID-19) in the given study is negatively impacting the country’s economic growth that converts into a global depression. The high incidence of poverty and social closeness increases more vulnerable conditions that spread coronavirus across countries. The momentous increase in healthcare expenditures put a burden on countries' national healthcare bills that stretch the depression phase-out of the boundary. The forecasting relationship suggested the negative impact of the coronavirus pandemic on the global economy over the next 10 years. The unified global healthcare policies, physical distancing, smart lockdowns, and meeting food challenges are largely required to combat the coronavirus pandemic and escape out from global depression.